We are your friends: a film of digital animation for children in chemotherapy treatment (Research, Society and Development, 2020)
The objective of this work is to describe the elaboration of a film of digital animation about the process of pediatric chemotherapy. As a method, it consists of a study of technology development, film of digital animation, based on existing manual in the Service of Hematology and Oncology of public institution specialized in the treatment of childhood cancer. For the development of the animation, three stages were followed: pre-production (script, storyboard), production and post-production. This product was built in a multidisciplinary field aimed at children undergoing cancer treatment and their families. As a results, we describe the steps of the creation of a product directed to children who receive the diagnosis of cancer and have their initiation in chemotherapy. The work is aimed at updating the printed manual, as well as transforming it into a digital animation film. The media was finished with 12 minutes and 22 seconds. Thus, it is believed that the educational technology in question acts as a strategic tool for health promotion and education, as well as an instrument to maximise the child’s understanding of the health/disease process and the importance of chemotherapy in the treatment of childhood cancer.